Лексико-семантическое пространство «позитивных и негативных эмоций» в видео вербальной коммуникации на примере англоязычных телесериалов «Друзья» и «Теория большого взрыва» - Клеблеева Резеда (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
This article examines the lexicon-semantic field of positive and negative emotions in the audiovisual communication of the English-language television series Friends and The Big Bang Theory. The study focuses on how emotional vocabulary is utilized to create character representations and dynamics in their interactions. Positive emotions, such as joy, friendship, and love, contribute to forming a warm atmosphere, while negative emotions, including anger, jealousy, and frustration, create conflict and drama. Non-verbal means play a crucial role in enhancing verbal expressions of emotions and adding depth to character perception. The article highlights the importance of emotional vocabulary in narrative construction and its impact on audience perception.